The Perfect Wudhu Practice as a Prevention Mechanism to Reduce the Covid-19 Virus Infection - Mohd Khalid, Halimi; Yunus, Zalilah Murni; Rusdi, Mikdar (Journal of Techno-Social, 2022)
The Covid-19 pandemic has changed the habitual practices of human life that have been practiced for so long. People all over the world have been introduced to a new form of habit termed the new norm. Several Standard Operational Procedures (SOP) have been introduced to curb the spread of this epidemic. However, the question arises whether these preventive measures are a new thing that has never existed before? Similarly, is there a similarity between the practice of SOP that must be on everyone today with the practices that have been practiced according to the disciplines of science and the religion of Islam. This study uses a qualitative method that uses the design of library research and document review. The results show that there are similarities between the practice of SOP outlined by the Ministry of Health Malaysia (MOH) and the World Health Organization (WHO) produced based on scientific studies with the practice of ablution that has long been organized by the holy religion of Islam. These findings have further added to the knowledge and confidence about the position of the disciplines of science and religion which are so beautifully complementary to each other. Further this evidence has directly rejected the ideas of dualism and secularism that separate religion from everyday life.